Gas Hydrate Equilibrium Measurement of Methane + Carbon Dioxide + Tetrahydrofuran+ Water System at High CO2 Concentrations. (2016) - Partoon, Behzad; Nashed, Omar; Kassim, Zamzila; Sabil, Khalik M.; Sangwai, Jitendra; Lal, Bhajan
Abstract: Application of gas hydrate in separation of carbon dioxide (CO2 ) form nitrogen in Carbon Capture and Storage (CCS) chain is recently studied by many researchers. Tetrahydrofuran (THF) is suggested as promoter for this process. The same process can be suggested for separation of CO2 from methane (CH4 ) for gas treatment and sweetening, especially for high CO2 content mixtures such as landfill gas. The first step in development of such process is understanding of the phase boundary of this mixture at different pressure-temperature condition and gas/liquid composition. In this work, gas hydrate phase boundary of CH4, CO2, THF and water at different pressure from 4.5 to 8.1 MPa is experimentally measured. CO2 mole fraction in gas phase is fixed at 0.7 and THF concentration in the liquid phase set at 0.03 mole fraction. Results show that presence of THF in the mixtures shift the phase boundary to the lower pressure / higher temperature condition. This effect is favorable for industrial applications.